2017
DOI: 10.3847/1538-4357/aa9521
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Low-energy Neutrinos Correlated with Gravitational Wave Events GW 150914, GW 151226, and GW 170104 with the Borexino Detector

Abstract: We present the results of a low-energy neutrino search using the Borexino detector in coincidence with the gravitational wave (GW) events GW150914, GW151226 and GW170104. We searched for correlated neutrino events with energies greater than 250 keV within a time window of ±500 s centered around the GW detection time. A total of five candidates were found for all three GW150914, GW151226 and GW170104. This is consistent with the number of expected solar neutrino and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Furthermore, since it has been shown recently from a binary neutron star merger that the resulting gravitational waves (GWs) Abbott et al [34] [35] arrive at essentially the same time (~1.7s) as the GRBs Goldstein et al [36] and Savchenko et al [37], this index of refraction for electromagnetic radiation would have to hold for gravitational waves as well! Consistent with this, the Borexino collaboration, as reported in d'Agostino et al [38], did not find any neutrinos above background correlated with the arrival of GWs. The only explanation that seems to embrace all these findings, as remarked in [5], is that one is possibly encountering consequences of that long-sought unified theory of electromagnetism and gravitation that might predict how dark energy could influence the propagation of EM radiation and GWs in this way.…”
Section: Resultssupporting
confidence: 69%
“…Furthermore, since it has been shown recently from a binary neutron star merger that the resulting gravitational waves (GWs) Abbott et al [34] [35] arrive at essentially the same time (~1.7s) as the GRBs Goldstein et al [36] and Savchenko et al [37], this index of refraction for electromagnetic radiation would have to hold for gravitational waves as well! Consistent with this, the Borexino collaboration, as reported in d'Agostino et al [38], did not find any neutrinos above background correlated with the arrival of GWs. The only explanation that seems to embrace all these findings, as remarked in [5], is that one is possibly encountering consequences of that long-sought unified theory of electromagnetism and gravitation that might predict how dark energy could influence the propagation of EM radiation and GWs in this way.…”
Section: Resultssupporting
confidence: 69%
“…As a further prediction, it is shown that the reduced speed of light leads to a redetermination of the Hubble constant, which in turn leads to a resolution of a long-standing difficulty concerning the age of the EdS universe. Since no dispersion was observed over the optical range in the SNe Ia studies [9] [10] [11], it was noted in [6] that if this held over the entire EM spectrum, as has now been shown to be the case, this would provide a simple explanation for the absence of neutrino correlation with GRBs found by IceCube [12] [13], which is further extended in this work to include the negative findings of Borexino [14] [15]. Additional references to other negative findings are also given below.…”
Section: Introductionmentioning
confidence: 76%
“…One possible explanation is that the sources of GRBs, although enormously energetic, do not produce a fluence of high energy neutrinos sufficient enough to be detected, and that the PeV neutrinos just happened to be passing through IceCube, is discussed in [13] with no way to check empirically. More recently, Borexino searched for neutrinos correlated with the arrival of GWs [15], but none were found, beyond solar and background neutrinos. Thus, it is sufficient for the above proposition to be valid, if the speed of the GRBs and the GWs through IGS is ~2c/3 for…”
Section: Absence Of Neutrinos Correlated With Grbsmentioning
confidence: 99%
“…Finally, gravitational waves from unknown or exotic sources (e.g., cosmic strings [12]) may be associated with neutrino bursts. Despite these possibilities, no neutrinos have been observed to date coincident with any gravitational wave event [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%